Design and Implementation of an Adaptive Space–Time Antenna Array for GPS Receivers - Li, Jianxing; Zhang, Ming; Shi, Hongyu; Zheng, Shi; Zhang, Anxue (Frequenz, 2015)
In this paper, an adaptive space–time antenna array to preserve global positioning system (GPS) signals while at the same time cancelling all interfering signals was designed and implemented. In the design, a new constraint vector and modified least mean square (M-LMS) algorithm were introduced and utilized to compute the real-time weights. An experimental system with a total size of 200 mm×200 mm×50 mm was implemented to verify the design. Design considerations and experimental results were presented and discussed. Experimental results show that high anti-jam capability has been achieved in the presence of wideband interfering signals. Therefore, the proposed design can be well applied for GPS receivers to enhance robustness.